Characterization of single vs. recurrent spontaneous coronary artery dissection. (February 2018) - Rigatelli, Gianluca; Dell'Avvocata, Fabio; Picariello, Claudio; Zuin, Marco; Giordan, Massimo; Roncon, Loris
Background: Spontaneous coronary artery dissection is a rare non-atherosclerotic cause of acute coronary syndromes, often underdiagnosed based on standard coronary angiography. Moreover, features, presentation, and intravascular imaging of recurrent spontaneous dissections have not been assessed. Methods: Patients with recurrent spontaneous coronary artery dissection, who were admitted to our catheterization laboratory over a 10-year period, were identified. Demographic, clinical, angiographic, and intravascular imaging data were reviewed and analyzed, comparing patients with a single event with those who had a recurrence. Results: Over the study period, 31 (0.2%, mean age 48.1 ± 8.8 years, 24 females) of 10, 954 patients who underwent coronary angiography experienced a single spontaneous coronary artery dissection, and 6 (0.05%, mean age 49.3 ± 10.1 years, 4 females) experienced recurrent spontaneous coronary artery dissection. No patient suffered more than 2 dissections. Arterial hypertension ( p  = 0.004), a string sign measuring >15 mm on angiography, and hematoma on intravascular ultrasound imaging were more frequently observed in patients with recurrent spontaneous coronary artery dissection. Conclusions: Hypertension, length of the string sign on angiography, and hematoma on intravascular ultrasound imaging might identify patients at higher risk of recurrent spontaneous coronary artery dissection despite a lifelong dual antiplatelet regimen.